ANALISA GAYA LAGU KLASIK GAMBANG KROMONG “POBIN KONG JI LOK’ - Imam Firmansyah (Narada : Jurnal Desain dan Seni, 2019)
Nowadays, the existing repertoire of the classic songs of gambang kromong is very apprehensive. Dozens of gambang kromong's classical songs developed comprehensively at the end of the 18th century, but in the present, there is only one song that is still possible to play, namely "Pobin Kong Ji Lok". Even, as a matter of fact, this song can only be played by an old music player. Based on the aforementioned problems, it is necessary to conduct documentation of "Pobin Kong Ji Lok" song, associated with an analysis of its musical style. "Pobin Kong Ji Lok" will be documented in the form of audiovisual, transcribed in the form of notation, then analyzed its style of music through the most prominent musical elements, including the musical scale, harmony, tuning system, rhythm, and the timbre of musical instruments.